The Relevance of Thimet Oligopeptidase in the Regulation of Energy Metabolism and Diet-Induced Obesity - Gewehr, Mayara C. F.; Teixeira, Alexandre A. S.; Santos, Bruna A. C.; Biondo, Luana A.; Gozzo, Fabio C.; Cordibello, Amanda M.; Eichler, Rosangela A. S.; Reckziegel, Patricia; Da Silva, Renee N. O.; Dos Santos, Nilton B.; Camara, Niels O. S.; Castoldi, Angela; et al. (Mdpi, 2020)
Thimet oligopeptidase (EC 3.4.24.15; EP24.15; THOP1) is a potential therapeutic target, as it plays key biological functions in processing biologically functional peptides. The structural conformation of THOP1 provides a unique restriction regarding substrate size, in that it only hydrolyzes peptides (optimally, those ranging from eight to 12 amino acids) and not proteins. The proteasome activity of hydrolyzing proteins releases a large number of intracellular peptides, providing THOP1 substrates within cells. The present study aimed to investigate the possible function of THOP1 in the development of diet-induced obesity (DIO) and insulin resistance by utilizing a murine model of hyperlipidic DIO with both C57BL6 wild-type (WT) and THOP1 null (THOP1(-/-)) mice. After 24 weeks of being fed a hyperlipidic diet (HD), THOP1(-/-) and WT mice ingested similar chow and calories; however, the THOP1(-/-) mice gained 75% less body weight and showed neither insulin resistance nor non-alcoholic fatty liver steatosis when compared to WT mice. THOP1(-/-) mice had increased adrenergic-stimulated adipose tissue lipolysis as well as a balanced level of expression of genes and microRNAs associated with energy metabolism, adipogenesis, or inflammation. Altogether, these differences converge to a healthy phenotype of THOP1(-/-) fed a HD. The molecular mechanism that links THOP1 to energy metabolism is suggested herein to involve intracellular peptides, of which the relative levels were identified to change in the adipose tissue of WT and THOP1(-/-) mice. Intracellular peptides were observed by molecular modeling to interact with both pre-miR-143 and pre-miR-222, suggesting a possible novel regulatory mechanism for gene expression. Therefore, we successfully demonstrated the previously anticipated relevance of THOP1 in energy metabolism regulation. It was suggested that intracellular peptides were responsible for mediating the phenotypic differences that are described herein by a yet unknown mechanism of action.
Keywords: obesity; insulin resistance; diet-induced obesity; proteasome; proteases; peptidases; mass spectrometry; peptidome